2023
DOI: 10.1186/s40164-023-00415-0
|View full text |Cite
|
Sign up to set email alerts
|

A new dosing regimen of ropeginterferon alfa-2b is highly effective and tolerable: findings from a phase 2 study in Chinese patients with polycythemia vera

Abstract: Ropeginterferon alfa-2b represents a new-generation pegylated interferon-based therapy and is administered every 2–4 weeks. It is approved for polycythemia vera (PV) treatment in the United States and Europe with a starting dose of 100 µg (50 µg for patients receiving hydoxyurea) and intra-patient dose titrations up to 500 µg at 50 µg increments, which took approximately 20 or more weeks to reach a plateau dose level. This study aimed to assess ropeginterferon alfa-2b at an alternative dosing regimen with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…We designed a phase II study to primarily evaluate whether initiating ropeginterferon alfa-2b at a higher dose with a simpler and faster intra-patient dose titration, i.e., the 250-350-500 µg dosing regimen, could result in an efficient CHR rate and molecular response (MR) in PV patients at 6 months based on the existing safety data in other indications for ropeginterferon alfa-2b, including viral hepatitis [21][22][23][24][25]. The results demonstrated that a CHR rate of 61.7% was achieved by this dose regimen in 6 months, which was notably higher than previously reported with the slow-titration schema [26]. However, the longer-term efficacy including CHR and MR, safety, and patient discontinuation rate needed to be investigated.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…We designed a phase II study to primarily evaluate whether initiating ropeginterferon alfa-2b at a higher dose with a simpler and faster intra-patient dose titration, i.e., the 250-350-500 µg dosing regimen, could result in an efficient CHR rate and molecular response (MR) in PV patients at 6 months based on the existing safety data in other indications for ropeginterferon alfa-2b, including viral hepatitis [21][22][23][24][25]. The results demonstrated that a CHR rate of 61.7% was achieved by this dose regimen in 6 months, which was notably higher than previously reported with the slow-titration schema [26]. However, the longer-term efficacy including CHR and MR, safety, and patient discontinuation rate needed to be investigated.…”
Section: Introductionmentioning
confidence: 83%
“…The CHR rates, based on the central laboratory assessments, at 12, 24, 36, and 52 weeks of the treatment were 44.9% [26], 61.2% [26], 69.4%, and 71.4%, respectively. Previously, a CHR rate of 43% following 1 year of treatment with ropeginterferon alfa-2b at the slow-titration schema was reported in the PROUD-PV study [16].…”
Section: Chr Rates Durability and Time To Chrmentioning
confidence: 98%
See 1 more Smart Citation
“…While our experience demonstrates that such combination is feasible and safe, the optimization of ropegIFNα2b use with avoidance of drug underdosing both at therapy start and in case of suboptimal response, could maximize the therapeutic bene t [16]. Indeed, higher doses of ropegIFNα2b recently showed a 61.2% of CHR rate at week 24, with acceptable but not negligible toxicity [17].…”
Section: Discussionmentioning
confidence: 99%
“…Interim data from a multicenter study in Korea and a phase II study in China suggest that an accelerated design regimen could be used, and the ECLIPSE-PV and EXCEED-ET Studies are also investigating an optimized dosing regimen (ClinicalTrials.gov Identifier: NCT05481151 and NCT05482971). 52 , 83 Blood counts are monitored every 2 weeks, and HU is tapered down on an individualized basis while the interferon dose is increased. For those on HU prior to initiating ropeginterferon alfa-2b-njft, taper the HU off by reducing the total biweekly HU dose by 20–40% every 2 weeks during weeks 3–12 with complete discontinuation of HU by week 13.…”
Section: Practical Management Of Interferon-based Therapiesmentioning
confidence: 99%